Energy Transfer Using Gradient Index Metamaterial - Boopalan Ganapathy; Subramaniam Chittur Krishnaswamy (International Journal of Antennas and Propagation)
The gradient refractive index structure in this paper is used to increase the quantum of energy transfer. This is done by improving the directive gain of the pyramidal horn antenna at a frequency of 10 GHz. A three-dimensional array of closed square rings is placed in front of the horn antenna aperture to form a gradient refractive index structure. This structure increases the directive gain by 1.6 dB as compared to that of the conventional horn antenna. The structure nearly doubles the wireless power transfer quantum between the transmitter and the receiver when placed at both ends. The increase in the directivity is achieved by converting the spherical wave emanating from the horn to a plane wave once it passes through the structure. This transformation is realized by the gradient refractive index structure being placed perpendicular to the direction of propagation. The gradient refractive index is constructed by changing the dimensions of a closed square ring placed in the unit cell of the array. The change in the refractive index gives rise to an improvement of the half power beam width and side lobe level compared to that of the normal horn. The design and simulation were done using CST Studio software.